Avaliação do efeito do borneol sobre a modulação autonômica da pressão arterial de ratos normotensos e com hipertensão renovascular - Luz, Mickael Sousa da (2021)
Borneol is a bicyclic monoterpene extracted essential oils of various medicinal plants. This compound has been used for a long time in traditional Chinese medicine with promising cardiovascular effects. Some studies have demonstrated the antioxidant, vasodilator and antihypertensive potential of borneol in normotensive animals and with L-NAME hypertension, however nothing has been reported about its effects on renovascular hypertension, as well as on the autonomic modulation of blood pressure and its control mechanisms. The present study aimed to evaluate the effects induced by borneol on cardiovascular parameters of normotensive rats and renovascular hypertension. For this, a combination of protocols in vivo was performed in SHAM and 2R1C rats, thus evaluating the effect of oral treatment for 14 days with borneol on blood pressure, heart rate, sympathetic and parasympathetic autonomic activity and baroreflex sensitivity. Oral treatment with borneol was able to reduce blood pressure only in 2R1C rats (2R1C + borneol: 123,12 ± 6 vs. 2R1C: 169,43 ± 9 mmHg, p <0,05), as well as decreased blood pressure systolic (2R1C + borneol: 144 ± 5,3 vs. 2R1C: 196 ± 11,39 mmHg, p <0,05) and diastolic (2R1C + borneol: 103,1 ± 4,5 vs. 2R1C: 154,9 ± 4,6 mmHg, p <0,05). The treatment did not cause significant changes in heart rate. When assessing autonomic function through the administration of pharmacological blockers, borneol did not induce changes in parasympathetic activity, however, it was able to reduce sympathetic hyperactivity in 2R1C rats (2R1C + borneol: -48,52 ± 7,289 vs. 2R1C: -73,43 ± 4,969 mmHg, p <0,05). Additionally, it also reduced the low frequency bands - LF (2R1C + borneol: 3,14 ± 0,29 vs. 2R1C: 9,69 ± 0,95 mmHg2, p <0,05), without showing any change in the high frequency bands. frequency - HF and sympathovagal index (LF/HF), supporting the reduction of sympathetic activity in 2R1C rats without interfering with parasympathetic activity. Moreover, oral treatment with borneol improved baroreflex sensitivity pharmacologically induced with vasoactive drugs (2K1C + Borneol: -3,6 ± 0,3 vs. 2K1C: -1,3 ± 0,1 bpm.mmHg-1, p <0,05), as well as spontaneous baroreflex (2R1C + borneol: -3,56 ± 0,64 vs. 2R1C: -1,38 ± 0,1 bpm.mmHg-1, p <0.05). Finally, oral treatment with borneol was not able to reduce oxidative stress serum. These data together suggest an antihypertensive effect of borneol, since it reduced blood pressure only in rats with renovascular hypertension. This effect may be related, in part, to the ability to reduce sympathetic activity and improve baroreflex sensitivity. This information makes borneol a molecule with an important future in hypertension therapy.